Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12864-016-3295-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals the genetic basis underlying the seasonal development of keratinized nuptial spines in Leptobrachium boringii

Abstract: BackgroundThe expression of sexually selected traits often varies with populations’ breeding cycles in many animals. The elucidation of mechanisms underlying the expression of such traits is a research topic in evolutionary biology; however, the genetic basis of the seasonal development of their expression remains unknown. Male Leptobrachium boringii develop keratinized nuptial spines on their upper jaw during the breeding season that fall off when the breeding season ends. To illuminate the genetic basis for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 81 publications
3
12
1
Order By: Relevance
“…Blast2GO identified more transcripts than Trinotate, and the taxonomic distribution of the BLAST hits differed between the two approaches, reflecting the inherent bias of species' representation in the Swiss-Prot database (which contains more than 20,200 H. sapiens sequences and approximately 6300 anuran sequences, but the latter representing few genera other than Xenopus). Approximately 34% of transcripts in the present assembly were annotated, within the range of values (32-57%) reported in similar studies [27,[35][36][37]. In D. chrysoscelis, the most common Metabolic Function category in the transcriptome was Catalytic, as also was observed in the transcriptome of the green-striped burrowing frog (Cyclorana alboguttata) [26].…”
Section: The Hepatic Transcriptome Of D Chrysoscelissupporting
confidence: 81%
See 2 more Smart Citations
“…Blast2GO identified more transcripts than Trinotate, and the taxonomic distribution of the BLAST hits differed between the two approaches, reflecting the inherent bias of species' representation in the Swiss-Prot database (which contains more than 20,200 H. sapiens sequences and approximately 6300 anuran sequences, but the latter representing few genera other than Xenopus). Approximately 34% of transcripts in the present assembly were annotated, within the range of values (32-57%) reported in similar studies [27,[35][36][37]. In D. chrysoscelis, the most common Metabolic Function category in the transcriptome was Catalytic, as also was observed in the transcriptome of the green-striped burrowing frog (Cyclorana alboguttata) [26].…”
Section: The Hepatic Transcriptome Of D Chrysoscelissupporting
confidence: 81%
“…As in other studies reporting amphibian transcriptomes [27,35,36], Cellular and Metabolic Processes were the most abundant Biological Process categories in the hepatic transcriptome of D. chrysoscelis. The present study focused on the hepatic transcriptome, whereas other studies have analyzed and reported a merged gene ontology classification of multiple tissues [27,35,36]; despite the distinct approaches and evolutionary histories of the species analyzed, the overall composition of the transcriptomes of D. chrysoscelis and these anurans is similar.…”
Section: The Hepatic Transcriptome Of D Chrysoscelissupporting
confidence: 76%
See 1 more Smart Citation
“…Although no response in tau was observed, we found increased genetic differentiation between the selection lines in the allele frequencies of genes related to a circadian entrainment KEGG pathways (Table S5). Interestingly, in another study, we did not find a difference in onset of activity (as a measure of entrainment) in a L:D cycle between the selection lines nor a clear genomic signal underlying the variation in the circadian traits studied (Laine, Atema, et al, 2019; (Audet et al, 2018), behaviour and in the HPGL axis especially during reproduction (Maffucci & Gore, 2009;Neal-Perry & Santoro, 2006;Zhang et al, 2016).…”
Section: Underlying Genomic Changesmentioning
confidence: 54%
“…One should note, however, that the genes investigated in differ from the genes in the circadian entrainment KEGG pathway, where the latter may thus give potential insights in genetic variation underlying phenotypic variation in circadian traits. Furthermore, neuronal and especially glutamate related GO groups and KEGG pathways are known to be important in learning (Audet et al 2018), behaviour (X. and in the HPGL axis especially during reproduction (Maffucci & Gore 2009;Neal-Perry & Santoro 2006;Zhang et al 2016).…”
Section: Underlying Genomic Changesmentioning
confidence: 99%